2020
DOI: 10.3390/su12010375
|View full text |Cite
|
Sign up to set email alerts
|

Nature Connection in Early Childhood: A Quantitative Cross-Sectional Study

Abstract: There have been calls to reconnect children with nature, both for their own wellbeing, as well as for ecological sustainability. This has driven the growth of outdoor and nature-schools for all ages, but especially in the early childhood education sector. However, to date, there has not been a quantitative study that looks at whether these settings actually promote nature connection. This paper aims to examine the role of nature nurseries in the promotion of connection to nature, when compared to traditional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 38 publications
1
27
0
4
Order By: Relevance
“…This study highlights that the ‘nature’ in ‘nature connection’ means different things in different locations … but it also shows what parents notice when their young children engage with nature. When Barrable and Booth (2020a) used the same index with parents of nursery children in Scotland, they found it a good fit for this sample too, which suggests that it captures some common features of parents' perspectives.…”
Section: Measuring Nature Connection In Childhoodmentioning
confidence: 91%
“…This study highlights that the ‘nature’ in ‘nature connection’ means different things in different locations … but it also shows what parents notice when their young children engage with nature. When Barrable and Booth (2020a) used the same index with parents of nursery children in Scotland, they found it a good fit for this sample too, which suggests that it captures some common features of parents' perspectives.…”
Section: Measuring Nature Connection In Childhoodmentioning
confidence: 91%
“…Against the hypotheses, none of the children's background characteristics, including sex, family's SES, parent's nature connectedness, or parent's visits in nature in free time, associated with a child's overall nature connectedness. In many of the previous studies teenager's proenvironmental values, attitudes, and behaviors have shown a correlation with their parent's proenvironmental values and behaviors (Barrable & Booth, 2020;Grønhøj & Thøgersen, 2017;Katz-Gerro et al, 2020;Leppänen et al, 2012;Li & Liu, 2016;Musitu-Ferrer et al, 2019). Thus, most surprisingly, not even the parent's nature connectedness associated with child's nature connectedness level in this study.…”
Section: Background Characteristics and Nature Connectednessmentioning
confidence: 39%
“…Nature connectedness. There are not currently any self-report questionnaires developed to evaluate nature connectedness in 6-to 7-year-old children (Barrable & Booth, 2020). However, The CNI questionnaire (Cheng & Monroe, 2012), which was originally developed for 8-to 10-year-old children, have demonstrated to be the most comprehendible and suitable also for 7-to 13-year-old children (Bragg, Wood, Barton, & Pretty, 2013).…”
Section: Ethics Statementmentioning
confidence: 99%
“…Working in natural environments promotes pupils' spirit of observation and study, and this contact with nature is necessary to analyze and systematize the information gathered later in another context [23]. This type of education allows children to reconnect with nature, both for their well-being and for ecological sustainability [24]. It is therefore clear that education has a key role to play in contributing to the achievement of the Sustainable Development Goals [25,26].…”
Section: Outdoor Educational Activities: Definition and Benefitsmentioning
confidence: 99%